Are prolactin serum levels and coronary artery atherosclerosis correlated in postmenopausal women? A cross-sectional study - Alireza Amirzadegan; Elnaz Salimi; Ali Hosseinsabet (KARE Publishing, 2019)
Objective: Prolactin is correlated with some conditions that predispose individuals to atherosclerosis. Prolactin receptors have been found in atherosclerotic plaques. However, the correlation between the serum prolactin level and the extension and severity of coronary artery atherosclerosis has yet to be studied. Methods: In total, 414 postmenopausal women candidated for selective coronary angiography with normal serum prolactin levels were enrolled. The patients' lipid profile and levels of serum prolactin, thyroid-stimulating hormone, C-reactive protein, urea, creatinine, and fasting blood sugar were measured. The Gensini score for each patient was calculated. The study population was divided into 3 groups according to the tertile of the serum prolactin level. Results: There was no statistically significant difference in terms of the Gensini score between the 3 groups in the univariate analysis (P = 0.075). The multivariable analysis showed that the serum prolactin level was not an independent determinant of the Gensini score (P = 0.430), whereas age, hypertension, diabetes and dyslipidemia were the independent determinants of the Gensini score. Conclusions: There was no statistically significant correlation between the serum prolactin level and coronary artery atherosclerosis expressed as the Gensini score in our sample of postmenopausal women.